Grb2 dimer interacts with Coumarin through SH2 domains: A combined experimental and molecular modeling study - Karoline Sanches; Raphael Vinicius Rodrigues Dias; Paulo Henrique da Silva; Marcelo Andrés Fossey; Ícaro Putinhon Caruso; Fátima Pereira de Souza; Leandro Cristante de Oliveira; Fernando Alves de Melo (Heliyon, 2019)
Grb2 is an important regulator of normal vs. oncogenic cell signaling transduction. It plays a pivotal role on kinase-mediated signaling transduction by linking Receptor Tyrosine kinases to Ras/MAPK pathway which is known to bring oncogenic outcome. Coumarins are phenolic molecules found in several plants and seeds widely studied because of the antibiotic, anti-inflammatory, anticoagulant, vasodilator, and anti-tumor properties. Despite several studies about the anti-tumor properties of Coumarin in vivo and the role of Grb2 in signaling pathways related to cell proliferation, a molecular level investigation of the interaction between Grb2 and Coumarin is still missing. In this study, we performed a combined set of biophysical approaches to get insights on the interaction between Grb2 in a dimer state and Coumarin. Our results showed that Coumarin interacts with Grb2 dimer through its SH2 domain. The interaction is entropically driven, 1:1 molecular ratio and presents equilibrium constant of 105 M−1. In fact, SH2 is a well-known domain and a versatile signaling module for drug targeting which has been reported to bind compounds that block Ras activation in vivo. Despite we don't know the biological role coming from interaction between Grb2-SH2 domain and Coumarin, it is clear that this molecule could work in the same way as a SH2 domain inhibitor in order to block the link of Receptor Tyrosine kinases to Ras/MAPK pathway.